Measuring the impact of the COVID-19 epidemic on university resumption and suggestions for countermeasures - Yin, Shi; Ma, Lijun; Dong, Tong; Wang, Ying (Frontiers in Public Health, 2022)
The resumption of classes in colleges and universities has a significant impact on epidemic prevention and control and campus public health security. For the healthy development of students and the prevention of the spread of the epidemic, universities must make a correct decision on whether to resume classes. The purpose of this study is to effectively assess the combined risk of university reopening due to the new crown epidemic to help universities make the right decision. This study firstly increases the number of indicators and improves the indicator system according to various factors involved in the process of resuming school. In this study, the pressure-state-response model was introduced to analyze the influencing mechanism among various factors and establish a comprehensive evaluation index system for the risk of university resumption. Secondly, the risk factors of disasters and the vulnerability of the disaster victims are used to measure the comprehensive risk degree of the epidemic, and the evaluation method of the comprehensive risk of school resumption in universities is put forward. Finally, empirical research is carried out. A university in Hebei province is taken as an example to verify the feasibility of the evaluation method. According to the evaluation results, the risk of resuming school is judged, and countermeasures and suggestions are put forward to reduce the risk of resuming school. The results show that the proposed system and the selected model can solve the problem well. This research can help universities to assess the risk of resuming school and make the right decision.